CORRELATION BETWEEN ENVIRONMENTAL FACTORS AND THE HUMAN DEVELOPMENT INDEX IN EAST JAVA IN 2019 - Nadiyah Firdaus; Airil Haimi Mohd Adnan (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2021)
Public health is influenced by environmental factors. The success of public health development can be seen from the Human Development Index (HDI). This research aims to analyze the relationship between environmental factors and the HDI in East Java in 2019. This research analyzed secondary data obtained from the East Java Provincial Health Office and published on the website of the Central Bureau of Statistics. Health Profile data in 2018 and the Human Development Index data in 2019 were used. This study used total sampling and selected all districts/cities in East Java (38 districts/cities). The Shapiro Wilk test (a sample of less than 50) was chosen to analyze the normality of the data and a Pearson correlation test was conducted to investigate the relationship between each variable. Based on our Pearson correlation analysis, we found several relationships between each variable. This study found that there is a relationship between access to decent drinking water and the HDI, as well as qualified latrines with the HDI, both with p-values of 0.000. Relationships were also found for healthy homes with the HDI with the p-value of 0.004, as well as qualified public places with the HDI with the p-value of 0.003. Finally, we found that there was no relationship between decent drinking water quality the HDI with a p-value of 0.821.